2021
DOI: 10.20886/ijfr.2021.8.1.23-35
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall Variability in Gunungsewu Karst Area, Java Island, Indonesia

Abstract: Karst area is highly susceptible to changes to climate parameters. One of the parameters is rainfall variability. In addition to shaping the condition of water resources, rainfall in the Gunung Sewu karst area determines the nature of crop and livestock of the agriculture sectors―the local population's main economic activities, warranting the significance of the rainfall variability studies. Rainfall variability in karst areas also affects disaster conditions such as drought and floods. However, due to insuffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…The multitemporal analysis in this research took seasons into account, given that rainfall is the main factor influencing variations in the spring's hydrological conditions. In the Gunungsewu Karst Area, the rainy season starts in October and ends in March, whereas the dry season lasts from April to September [25]. Figure 2 shows four charts illustrating the correlations between phosphate, flow discharge, and rainfall in different seasons.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The multitemporal analysis in this research took seasons into account, given that rainfall is the main factor influencing variations in the spring's hydrological conditions. In the Gunungsewu Karst Area, the rainy season starts in October and ends in March, whereas the dry season lasts from April to September [25]. Figure 2 shows four charts illustrating the correlations between phosphate, flow discharge, and rainfall in different seasons.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, both R-values indicated weak correlations,suggesting that the three pollutants did not originate from the aforementioned sources. According to previous studies by Cahyadi et al [7] at the Selonjono Spring and Adji et al [30] in the Seropan Underground River in the Gunungsewu Karst Area, phosphate comes from agricultural fields, sulfate from domestic waste (gray water or detergent), and nitrate possibly from fecal matter. Agricultural practices apply fertilizers that leave residues of phosphate in the soil, and Loganathan et al [31] confirmed that the groundwater's phosphate content is likely to increase with the added fertilizers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The volcanoes in Indonesia are unique compared to those found in other parts of the world. Cahyadi et al (2021) stated that these are usually located on the Indonesian Maritime Continent, and it affects the high rainfall triggered by Monsoons, El Niño Southern Oscillation (ENSO), and Inter Tropical Convergence Zone (ITCZ) (Aldrian & Susanto, 2003). Döll and Fiedler (2008) reported that the high tropical rainfall impacts the potential for groundwater recharge, especially in volcanoes.…”
Section: Introductionmentioning
confidence: 99%
“…
Landscape is very dynamic [1,2,3]. In line with the development of an increasingly climate change [4] and high population, the dynamics of the landscape have also changed due to an increase in the intensity of the population in utilizing land. The condition of the corona virus pandemic since the beginning of 2020 has resulted in two impacts to the environment.
…”
mentioning
confidence: 99%